Rarity and nutrient acquisition relationships before and after prescribed burning in an Australian box-ironbark forest. Issue 3 (16th May 2018) - Patykowski, John; Dell, Matt; Wevill, Tricia; Gibson, Maria
Abstract: Nutrient cycling is greatly influenced by dominant plants that contribute high amounts of leaf litter to soils; however, less-dominant and rare species can play keystone roles in nutrient cycling if they have unique nutrient acquisition traits and provide high-quality litter. In many parts of the world, wildfire is likely to become more frequent and intense under a changing climate. The effect this will have on plant rarity and on species with unique nutrient acquisition traits, and thus nutrient cycling, remains poorly understood. Working within an Australian box-ironbark forest, we determined if a relationship existed between species rarity and the uniqueness of their leaf nutrient profiles, and if this relationship changed after prescribed burning. We created an index of species rarity from a data set of woody perennial species abundance in areas before and after autumn or spring burns, or left unburnt. We created indices of uniqueness for the leaf nutrient profiles of 42 woody perennial species occurring in the ecosystem, based on amounts of six macronutrients and four micronutrients found in fresh and senesced leaves of each species. Five nutrient acquisition strategies (mycorrhizal, N-fixing, carnivorous, hemiparasitic and proteoid roots) were represented in the data set. There was no community-wide relationship between rarity and uniqueness of leaf nutrient profiles, and this did not change as a result of fire. However, two hemiparasitic species were relatively rare in the ecosystem studied, and differed greatly from other species due to high K and P in senesced leaves. Thus, some of the rarest species, such as hemiparasites, can be functionally unique. Understanding the functional characteristics of rare species is important so that unique functional contributors can be identified and conserved to prevent local extinction. Abstract : We examined the relationship between nutrient acquisition strategies, senesced leaf nutrient profiles and species rarity before and after prescribed burning in a nutrient-poor box-ironbark forest in southeastern Australia. While no community-wide relationship between rarity and uniqueness of leaf nutrient profiles was found, some of the rarest species were functionally unique. Two hemiparasitic species were relatively rare in the ecosystem studied, and differed greatly from other species due to high concentrations of phosphorous and potassium in senesced leaves. Our study highlights the importance of identifying and ultimately conserving species with unique traits to prevent loss of functional contributions.